Implementasi Jaminan Keselamatan Dan Kesehatan (K3) Pada Pekerja Work From Anywhere (WFA) - Hasna Nurul Zahida; Andriyanto Adhi Nugroho (Fakultas Hukum, Universitas Warmadewa, 2024)
The Work From Anywhere (WFA) work system implemented by some companies allows workers to work from various places, which can become workplaces for them. In reality, each location has various potential risks of work accidents, especially if the place is not suitable for work, and often workers are not aware of the risks that may exist. The purpose of this research is to analyze the application of Occupational Safety and Health (OHS) Guarantees for Work From Anywhere (WFA) workers. This research uses an empirical juridical method with a focus on statutory analysis using a conceptual approach, because all data collected through interviews. Data is obtained through interviews with workers who undergo the WFA work system in various companies in Indonesia. The results show that there is currently no expansion of the regulations that have been adopted by the Ministry of Manpower that cover all types of work, including those undergoing WFA. In addition, companies that implement WFA only provide personal insurance to their workers, without clear provisions regarding the application of work in situations where workers experience work accidents while undergoing WFA.